2016
DOI: 10.1016/j.jcin.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Bivalirudin and Radial Access in Acute Coronary Syndromes Is Not Superior to the Use of Either One Separately

Abstract: Bivalirudin reduces bleeding risk only with femoral access, and radial access reduces bleeding risk only with heparin anticoagulation. Therefore, there is no additional benefit to the combined use of bivalirudin and radial access strategies in patients with ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The need for GPIs in primary PCI is a matter of ongoing discussion . However, data suggest that beneficial effects of bivalirudin are larger if studies with high rates of GPIs are analyzed. Different studies observed beneficial effects of bivalirudin in transfemoral, but not in transradial interventions . The high rate of transfemoral access in the BSR might be one factor supporting beneficial effects of bivalirudin on bleeding rates.…”
Section: Discussionmentioning
confidence: 95%
“…The need for GPIs in primary PCI is a matter of ongoing discussion . However, data suggest that beneficial effects of bivalirudin are larger if studies with high rates of GPIs are analyzed. Different studies observed beneficial effects of bivalirudin in transfemoral, but not in transradial interventions . The high rate of transfemoral access in the BSR might be one factor supporting beneficial effects of bivalirudin on bleeding rates.…”
Section: Discussionmentioning
confidence: 95%
“…Despite its limitations, UFH it still considered a Class I indication for anticoagulation in patients undergoing PCI . Recent meta‐analyses have demonstrated similar MACE and NACE rates between bivalirudin and UFH (particularly when accounting for concomitant GP IIb/IIIa inhibitors) among higher acuity ACS patients undergoing PCI via transradial approach, and using more potent antiplatelet therapy . However, previous randomized trials that enrolled mainly patients with ACS demonstrated a significant reduction of access site and non‐access site bleeding complications in patients treated with bivalirudin as compared with patients treated with UFH and GP IIb/IIIa inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the arterial access site on bleeding complications is increasingly scrutinized. Meta‐analysis conducted by Mina et al, suggested bivalirudin was associated with fewer bleeding events only when femoral access was employed, whereas radial access bleeding was only reduced with the utilization of UFH among patients with ACS . Most recently, the large scale randomized superiority trial Minimizing Adverse Hemorrhagic Events by Transradial Access Site and Systemic Implementation of Angiox (MATRIX Access) compared radial to femoral approaches in 8404 ACS patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…The elderly subgroup analysis demonstrated a superior effect of transradial access driven by a reduction in major access site complications of 3.6% vs 6.6% p  = 0.03 [11]. However, when the radial approach fails, the femoral approach with bivalirudin has proven to yield similar bleeding rates compared with radial access and using heparin in a meta-analysis of eight randomised trials including 27,491 ACS patients [12]. …”
Section: Step Two: Measures To Reduce Bleeding Riskmentioning
confidence: 99%